"Do I feel safe revealing this information to you?": Patient perspectives on disclosing sexual orientation and gender identity in healthcare. Issue 6 (17th August 2020) - Ogden, Shannon N.; Scheffey, Kathryn L.; Blosnich, John R.; Dichter, Melissa E.
Abstract: Objective: To examine university student perspectives on, and experiences with, disclosing sexual orientation and gender identity (SO/GI) in healthcare. Participants: Thirty-four graduate and undergraduate students from a large mid-Atlantic city in the United States participated in 1 of 6 focus groups held from October 2017 to February 2018. Methods: Focus groups were audio-recorded and transcribed verbatim. Transcripts were analyzed using thematic analysis and principles of grounded theory to identify emerging themes. Results: Patient considerations around disclosing SO/GI fell within three thematic categories: the relevancy of SO/GI information to the clinical encounter, the patient–provider relationship, and concerns about negative provider reactions to disclosure. Conclusions: Findings highlight the need for provider understanding of SO/GI diversity and establishing safe and comfortable environments to facilitate disclosure for young adult patients. Lack of sensitivity to patients' experiences may exacerbate health disparities among sexual and gender minorities by failing to collect accurate epidemiological data and discouraging seeking care.